OH defects in coesite and stishovite during ultrahigh-pressure metamorphism of continental crust - Frigo, Corinne; Stalder, Roland; Ludwig, Thomas (Physics and chemistry of minerals, 2019)
The high-pressure silica polymorphs coesite and stishovite were synthesized under water-saturated conditions from a natural granitic composition doped with Li and B. Experiments were performed in a Multi-Anvil apparatus between 4 and 9.1 GPa and 900 and 950 °C, based on the conditions of a subducting continental crust as realistic for the ultrahigh-pressure metamorphic units Dora Maira and Kochetav massifs. Run products consisted of coesite/stishovite + kyanite ± phengite ± omphacite, and quench material. The synthesized silica polymorphs were successively analyzed by infrared spectroscopy, electron microprobe, and Secondary-Ion Mass Spectrometry (SIMS). No hydrous defects were observed in coesite synthesized at 4 GPa and 900 °C, whereas coesite grown at higher pressures revealed a triplet of infrared absorptions bands at 3575, 3523, and 3459 cm− 1, two minor bands at 3535 and 3502 cm− 1, and a small band at 3300 cm− 1 that was only visible at 7.7 GPa. The total amount of Al was charge-balanced by H and the other monovalent cations. However, the band triplet could not be associated with AlOH defects, while the band doublet was inferred to BOH defects and the small band probably corresponded to interstitial H. Stishovite displayed one dominant band at 3116 cm− 1 with a shoulder at 3170 cm− 1, and a minor band at 2665 cm− 1, probably all associated with AlOH defects. BOH defects were not observed in stishovite, and LiOH defects were neither observed in coesite nor stishovite, probably because of preferentially partition of Li in other phases such as omphacite. The total amount of defect protons increased with pressure and with metal impurity concentrations. The general increase in OH defects in silica polymorphs with increasing pressure (this study) contrasted the negative pressure trend of OH in quartz observed previously from the same starting material, and revealed an incorporation minimum of OH in silica polymorphs around the quartz/coesite phase transition.
First online: 26 July 2018
Gesehen am 14.10.2019